On the Transformative Potential of the Elite Groups in Shaping Societies: The Case of Islahi - Rauf, Abdul; Amin, Husnul (Islamic Studies, 2013)
In a political sociology setting, this research concerns the central location of elite groups in relation to the non-elite sections of society in the process of social change. It does so by focusing on the ideas and approach of an eminent reformist scholar and once staunch Islamist ideologue, Amin Ahsan Islahi. Studies on elites abound in the social sciences literature due to elite’s conceivable roles and effects in/on societies. Muslim intellectuals across the world, both from the traditional as well as reformist circles, have addressed the significance of elites in shaping their respective societies, and consequently the primacy of attention they needed to receive. However, a systematic account of how diverse religious scholarship has addressed the role and function of elite in bringing about their imagined social change, is missing from the social science literature. This paper highlights the contribution of one such scholar from the subcontinental Muslim tradition about a criticism on the existing mode of preaching and the importance of elites and why they should be given priority over masses by the preachers and pro-reform actors.